Redefining Language Learning: Embedding TELL in the Outcome-Based Education Syllabus - Rochmahwati, Pryla; Kasnun; Darrin Zuhri, Muhammad (Universitas Negeri Semarang, 2025)
The integration of technology in language learning has become increasingly relevant, especially in the context of Outcome-Based Education (OBE) frameworks. The present study scrutinized the integration of Technology-enhanced language learning (TELL) within the Outcome-Based Education (OBE) framework in the English department’s Integrated course syllabus. This study employed the qualitative method to explore the technology tools used to promote language competency and their corresponding link to measurable learning outcomes through document analysis and students and lecturer interviews. Results of the study revealed that by using digital tools like Google Docs, Padlet, Kahoot, and Flipgrid, students contribute to interactive and collaborative learning activities to develop their language skills - listening, speaking, reading, and writing skills. Then, challenges related to technical issues were found, such as poor internet connectivity and difficulties with unfamiliar platforms, limiting the full potential of the technological integration. Ultimately, this research seeks to contribute to the ongoing development of language education by optimizing technology use to meet educational goals and improve learning outcomes.